Diagnosis of research training in Stomatology studies in "Raúl González Sánchez" Faculty - Sol Ángel Rosales Reyes; Maillorys Ruano Ortega; Edelis Raimundo Padrón; Orietta Valverde Grandal; Teresa Sanz Cabrera (Editorial Ciencias Médicas, 2013)
Introduction: the considerations of the students and graduate about the training received and the results of the products of research activity are important sources for the diagnosis of the research training offered in the universities studies. Objective: to diagnose the current state of research training in students and graduate from "Raúl González Sánchez" Faculty Methods: a cross-sectional study of the variable research training was conducted. A questionnaire was applied to the 22 % of 5th Year students and 51 graduates of Stomatology in the faculty. A review of the marks given to the final works was made in the subject History of Cuba for the students of the 2nd, 3rd and 4th Years of the studies and also, to the scientific papers presented by the students in the Scientific Event held in the 2011-2012 academic year; this review was made with the objective to determine the principal limitations presented. Percentage was used as summary measure. Results: the 8.6 % of those polled considered that the training received for research function was insufficient, the 42 % considered it as regular. The 22 % got regular marks in the final works of different subjects. 86 works were presented in the Students Scientific Event held in the 2011-2012 academic year, participating only the 24.3 % of the students. None of the works presented in the evaluation got the highest mark. Conclusions: more than half of those polled considered the training received as regular and insufficient. There was low participation of the students in the Students Scientific Event. The difficulties in the works presented in the event and the final works of the subjects are evidences of the insufficient training of the students in research activity. Key words: research training, satisfaction with research training, Students Scientific Event, research work.